Chemical and biological properties of soils in milpa interlaced with fruit trees - Arriaga-Vázquez, Ana Magdalena; Martínez-Menez, Mario Roberto; Rubiños-Panta, Juan Enrique; Fernández-Reynoso, Demetrio Salvador; Delgadillo-Martínez, Julián; Vázquez-Alarcón, Antonio (REVISTA TERRA LATINOAMERICANA, 2020)
The agricultural management of the soil in zones of hillside of the rain forest of Mexico, determines erosion and changes on physical and biological soil properties. The objective of this research was to evaluate the chemical and biological characteristics, in the milpa intercropped system in fruit trees (MIAF) and compare this with traditional agricultural and conservation tillage systems. The soils of the donor and recipient parts of the MIAF, of the traditional milpa and of the manageable with conservation tillage, are sampled; the chemical and biological characteristics in the soils of Axochío, San Andrés Tuxtla, Veracruz. The results indicate that the MIAF system improves groups of microorganisms, in addition to a pH closer to neutrality, higher content of organic matter, inorganic N, total N, total P, extractables P and K in f ilter zone.